The endless wait of bureaucracy - UiTM, MITASA (Kesatuan Kakitangan Akademik UiTM (MITASA), 2025)
For many of us at UiTM, bureaucracy is a lived reality rather than only a term. What should be simple tasks often become a marathon of forms, signatures, and follow-ups. One colleague shared that her promotion application sat in different offices for years, with the same response each time: "It's still in process." By the time the approval came, the excitement had long disappeared. These are not isolated experiences. From promotions to study leave, claims to repeated amendments, bureaucracy has become a test of patience for staff across all levels.